Geopolymers Based on a Mixture of Steel Slag and Fly Ash, Activated with Rice Husks and Reinforced with Guadua angustifolia Fibers (2023)
At present, the conservation of the environment represents an objective that everyone wants to achieve. The construction industry has influenced the advancement of alternative materials that comply with sustainable development. In this article, reinforced concrete was obtained by mixing 80% blast furnace slag and 20% fly ash. These concentrations were chosen because they provide the lowest porosity in the cementitious matrix. Rice husk ash was used as an activator. Guadua angustifolia fibers were used to evaluate the mechanical performance of the concrete. The composition of the raw material was determined by X-ray fluorescence, the microstructure of the fibers by AFM, and the SEM technique was used to determine the surface characteristics of guadua fibers and concrete mixes. The structural characterization using XRD, the structure of the molecules of the guadua fiber, and the composition of the mixture’s molecular mixtures were determined by FTIR spectroscopy. Its properties, such as tensile strength and flexural strength, were analyzed. The results indicated that the concrete with the addition of Guadua angustifolia fibers. The results indicated that the concrete with the addition of guadua angustifolia fibers showed the best mechanical behavior. Tensile strength was optimized, establishing values of 2.68 MPa for unreinforced concrete and up to 3.12 MPa for fiber-reinforced concrete. The flexural strength values increase at ages after 28 days due to the pozzolanic reaction generated. Values of 2.8 MPa were obtained for concrete without fiber and 3.5 MPa for concrete reinforced with guadua angustifolia fiber.